Distribution Patterns of DNA N6-Methyladenosine Modification in Non-coding RNA Genes - Li, Yu; Zhang, Xiao-Ming; Luan, Mei-Wei; Xing, Jian-Feng; Chen, Jianguo; Xie, Shang-Qian (Frontiers in Genetics, 2020)
N6-methyladenosine DNA modification (6mA) played an important role in epigenetic regulation of gene expression. And the aberrational expression of non-coding genes, as important regular elements of gene expression, was related to many diseases. However, the distribution and potential functions of 6mA modification in non-coding RNA genes are still unknown. In this study, we analyzed the 6mA distribution of non-coding RNA genes and compared them with protein-coding genes in four species (Arabidopsis thaliana, Caenorhabditis elegans, Drosophila melanogaster and Homo sapiens) using single-molecule real-time (SMRT) sequencing data. The results indicated that the consensus motifs of short nucleotides at 6mA location were highly conserved in four species, and the non-coding gene was less likely to be methylated compared with protein-coding gene. Especially, the 6mA-methylated lncRNA genes were expressed significant lower than these genes without methylation in A. thaliana (p = 3.295e-4), D. melanogaster (p = 3.439e-11) and H. sapiens (p = 9.087e-3) all four species. The detection and distribution profiling of 6mA modification in non-coding RNA regions from four species reveal that 6mA modifications may have effects on their expression level.